Gorham–Stout disease: good results of bisphosphonate treatment in 6 of 7 patients. (3rd March 2020) - Schneider, Kristian Nikolaus; Masthoff, Max; Gosheger, Georg; Klingebiel, Sebastian; Schorn, Dominik; Röder, Julian; Vogler, Tim; Wildgruber, Moritz; Andreou, Dimosthenis
Abstract : Background and purpose — Gorham–Stout disease (GSD) is a rare mono- or polyostotic condition characterized by idiopathic intraosseous proliferation of angiomatous structures resulting in progressive destruction and resorption of bone. Little is known about the course of disease and no previous study has evaluated patients' quality of life (QoL). Patients and methods — This is a retrospective analysis of 7 consecutive patients (5 males) with a median age at diagnosis of 14 years and a median follow-up of 7 years who were diagnosed with GSD in our department between 1995 and 2018. Data regarding clinical, radiographic, and histopathological features, and treatment, as well as sequelae and their subsequent therapy, were obtained. QoL was assessed by Musculoskeletal Tumor Society Score (MSTS), Toronto Extremity Salvage Score (TESS), and Reintegration to Normal Living (RNL) Index. Results — 3 patients had a monoostotic and 4 patients a polyostotic disease. Besides a diagnostic biopsy, 4 of the 7 patients had to undergo 8 surgeries to treat evolving sequelae. Using an off-label therapy with bisphosphonates in 6 patients, a stable disease state was achieved in 5 patients after a median of 20 months. The median MSTS, TESS, and RNL Index at last follow-up was between 87% and 79%. Interpretation — Due to its rare occurrence, diagnosis and treatment of GSD remain challenging. Off-label treatment with bisphosphonates appears to lead to a stable disease state in the majority of patients. QoL varies depending on the individual manifestations but good to excellent results can be achieved even in complex polyostotic cases with a history of possibly life-threatening sequelae.